Al-Qur'an Sebagai Inspirasi Peradaban: Tinjauan Historis, Epistemologis, dan Etika Universal - Bina Prima Panggayuh; Firman Aditiya; Keysha Ayu Pradiameka; Nadira Putri Emma; Syifa Hafifah Nufus (Yayasan Al-Afif, 2025)
This study investigates the Qur’an as a central foundation in the formation of Islamic civilization by highlighting its role in guiding moral conduct, shaping intellectual traditions, and directing social development. The objective of this research is to clarify how Qur’anic teachings can be reinterpreted and implemented to support the advancement of a modern society that upholds ethical values and scientific growth. The research employs a descriptive qualitative design through an extensive review of literature, including scholarly publications on Islamic civilization, Qur’anic thought, and universal ethical frameworks. The findings indicate that the Qur’an has historically encouraged intellectual exploration, the establishment of social norms, and the development of moral awareness through an integrative epistemology that unites revelation, reason, and empirical observation. Furthermore, the Qur’an provides principles that remain relevant in addressing contemporary global issues such as justice, coexistence, and human dignity. The study concludes that contextualizing Qur’anic values through an integrative approach can offer a constructive framework for building a modern civilization that harmonizes technological progress with ethical responsibility. The proposed framework underscores the need to align Qur’anic principles with present-day societal challenges.